Starch/chitosan nanoparticles bionanocomposite membranes for methylene blue dye removal - Ilias, Hanis Masyithah; Othman, Siti Hajar; Ahmad Shapi’i, Ruzanna; Md Yunos, Khairul Faezah (Institute of Physics, 2024)
This research aims to develop relatively new membranes from starch biopolymer incorporated with different concentrations (0, 5, 10, 15, 20% w/w of solid starch) of chitosan nanoparticles (CNP) that can be used for water treatment. The membranes were fabricated using the solvent casting method while the CNP was produced using the ionic gelation method. The membranes were characterized in terms of morphology, porosity, water vapor permeability (WVP), and water contact angle. The application of the membranes to treat water was demonstrated on methylene blue solution because methylene blue is a commonly used dye in many industries. It was found that the starch/10% CNP membrane was the optimum membrane for methylene blue dye treatment because the membrane exhibits a smooth surface, high WVP (1.67 × 10−10 g Pa−1 h−1 m−1), high porosity (59.92%), low water contact angle value (44.8°), and resulted in the highest percentage removal of methylene blue (94.0%) after the filtration. After filtration, the starch/10% CNP membrane was still in good condition without breakage. In conclusion, the starch/CNP membranes produced in this study are promising for sustainable and environmentally friendly water treatment, especially for water containing methylene blue dye. This research aligns with current thematic trends in bionanohybrid composite materials utilization, offering innovative solutions for addressing water pollution challenges.